Flow Cytometry and T-Cell Response Monitoring after Smallpox Vaccination - Poccia, Fabrizio (Centers for Disease Control and Prevention, 2003)
Orthopoxvirus zoonosis or smallpox as result of bioterrorism or biological warfare represents a risk for epidemic spread. By monitoring T-cell responses by flow cytometry, we observed a recall response after recent vaccination against smallpox. When the high similarity between the orthopoxviruses is considered, this rapid assay that uses vaccinia antigens could identify recently exposures.